A superstructure based optimisation approach for regeneration reuse water network with a detailed nanofiltration model - Jakata, Nyasha Valerie Pemberai J (My University, 2022)
Increasing costs of purchasing freshwater, coupled with environmental sustainability concerns, have necessitated the adoption of innovative strategies for reducing freshwater consumption and effluent water discharge in chemical processes. Regeneration technologies partially purify process wastewater, thereby increasing opportunities for its reuse and recycle. Nanofiltration has emerged as a competitive wastewater regeneration technology. However, the optimal design of nanofiltration networks has not been extensively investigated. This study presents a framework for the optimal design and synthesis of multicontaminant nanofiltration membrane regenerator networks for application in water minimisation problems. The mathematical optimisation technique is developed based on a superstructure containing all system components and streams, incorporating nanofiltration units, pumps and energy recovery devices. A linear black-box approach and a detailed approach using the Spiegler-Kedem model are explored in modelling the nanofiltration, and the steric-hindrance pore model is used to characterise the membrane. The objective of the optimisation is to simultaneously minimise the water consumption and the total annualised cost of the network. Furthermore, the optimal size, configuration, membrane properties and operating conditions of the equipment are determined. The applicability of the model is illustrated using a case study of an integrated pulp and paper plant. The customized, detailed design of the regenerator network increased freshwater savings by 24% when compared to a black-box model, 31% when compared to a detailed model with fixed module specifications and 41% when compared to a reuserecycle system with no regeneration. Similarly, cost savings of 38%, 35% and 36% respectively were obtained. It was found that detailed models are preferable when compared to the linear black-box approach. It was also found that the customised design of regenerator models significantly increased the opportunity for environmental and cost savings when compared to the use of pre-selected modules.
A dissertation submitted in fulfilment of the requirements for the degree of Master of Science in Engineering to the Faculty of Engineering and the Built Environment, School of Chemical and Metallurgical Engineering, University of the Witwatersrand, Johannesburg, 2022